News Writing of Child Accident in Harian Metro Newspaper Online - Sharil Nizam, Sha’ri; Nurul Afikah, Azar; Nurul Fadzlin, Mohd Asri; Nor Azuan, Ahmad; Zuraini, Seruji; Azean Idruwani, Idrus (Human Resource Management Academic Research Society, 2020)
The aim of the current study is to investigate the child accidents news through the Harian Metro newspaper online.The main justification for this research is a good news holistically must have multiple element such as who, when, where, why and how in the newspaper (Chamil Wariya, 2008). Without a valid fact and six elements of a news item, undoubtedly readers having some difficulties to understanding the reported issue.Two objective of this study are Identify the elements of who, what, why, when, where and how in the Harian Metro children's accident news, and elemental analysis of who, what, why, when, where and how in the Harian Metro children's accident news.Selection of research data was conducted from June till September 2018 because a lot of news on child accidents were reported due that period. Thus, an overall of 17 sample news topics were selected to identify the element of what, who, when, where, why and how to analyze based s content analysis. Descriptive qualitative analysis was used to analyze the result. The findings of the main study show the six elements of news namely what, where, who, when, why and how often frequently used in news involving tragedy or child accident. The elements of how it is used in this type of news to tell the community about a tragedy or accident that happened more clearly and refer to authorities such as the police.